Falando de Diderot... - Gonçalves, Vera Teresa Valdemarin [UNESP] (Universidade Estadual Paulista (Unesp), 1984)
A leitura de textos de Direrot, no contexto da Revolução Francesa e discussão do papel do crítico e ativista nas transformações sociais.

A reading of Diderot in the context of the French Revotution and a discussion of the role of the critic and of the a activist in the social transformations.
Speaking of Diderot...
Keywords: Revolução Francesa; ativista; burguesia